Using spent fluid catalytic cracking (fcc) catalyst as pozzolanic addition — a review (2010)
Spent fluid catalytic cracking (FCC) catalyst is an oil industry by product from fluidised-bed catalytic cracking units. This residue is mainly formed by an active component (faujasite type zeolite Y) in an amorphous aluminosilicate matrix. It mainly consists of up to 90% silica and alumina. This paper reports an extensive literature review regarding the characterisation and mechanical and durability properties of mortar and concrete added to this material. FCC has been studied lately due to its pozzolanic characteristics and the good performance of concrete mixtures using FCC as cement replacement.